Wpływ jednomandatowych okręgów wyborczych na wyniki wyborów do rad gmin w gminach powyżej 20 tys. mieszkańców - Mielewczyk, Jakub (Refleksje. Pismo naukowe studentów i doktorantów WNPiD UAM, 2018)
The aim of this article is to analyze the impact of changes in the electoral formula on the results of local elections in municipalities with more than 20,000 inhabitants. In this municipalities, existing proportional formula was replaced by FPTP system with single member districts. In this study, author makes a comparative analysis of the results of the municipal councils elections since 2002. Empirical analysis is based on quantitative data of the National Electoral Commission. The research proves that the change of the electoral formula was important factor which affected the results of the elections in the municipalities with more than 20,000 inhabitants.